Pengaruh Brand Image Terhadap Keputusan Menggunakan Aplikasi Go-Jek pada Mahasiswa Fispol Unsrat Manado - Kuheba, Mahendra R.; Manoppo, Wilfried S.; Tumbel, Tinneke M. (Productivity, 2020)
This study aims to determine the effect of Brand Image on the Decision to Use the Go-Jek Application in Manado’s FISPOL Students. Brand Image Variables are Tested using 3 indicators and Decision Variable Using Go-Jek uses 7 indicators. This research methodology uses a quantitative research approach. The sampling technique used was a random sampling method with a population of 3314 respondents. In determining the sample size of this study determined by the solving technique and obtained a sample of 100 respondents. Data collection techniques were carried out by conducting observations in the field and distributing respondents’ questionnaires, using correlation analysis and simple linear regression. The result of R between the two variables is 0.802, meaning the relationship between brand image and the decision to use Go-Jek is very strong. Then the value of R square (determinant coefficient) of 0.643. This shows that the decision to use Go-Jek in Manado’s FISPOL Unsrat 64.3% is influenced by brand image, while the other 35.7% is determined by other factors not examined in this study.Â